Hungarian Monitoring, 12 August 1988 . [Magyar rádiófigyelő], 1988. augusztus 12 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - USSR: Soviet shadow economy; gang warfare - Poland: Jaruzelski meets Cardinal Glemp Domestic Affairs: - Government spokesman on government's duties - Success of Budapest McDonald's - Rapid fall in living standards Economy: - World Bank loan to develop foodstuffs market - Brining foreign capital in to help develop trade services and tourism in Budapest Külpolitika: - SZU: szovjet árnyékgazdaság; galerik háborúja - Lengyelország: Jaruzelski találkozója Glemp bíborossal Belpolitika: - A kormányszóvivő beszél a kormány feladatköréről - A budapesti McDonald's sikere - Zuhanó életszínvonal Gazdaság: - Világbanki hitel az élelmiszergazdaság fejlesztéséért - A főváros kereskedelmi ellátottságának és idegenforgalmának fejlesztése külföldi tőke bevonásával